Distribution and Characterization of Kepone-Resistant Bacteria in the Aquatic Environment - Orndorff, S. A. (1980)
Effects of the chlorinated insecticide Kepone on the ecology of Chesapeake Bay and James River bacteria were studied. Kepone-resistant bacteria present in a given environment were found to reflect the degree of fecal and/or high organic pollution of the sampling sites, based on total numbers and generic composition of the populations of Kepone-resistant bacteria. The presence of Kepone-resistant bacteria was found to be correlated (α = 0.01) with total coliforms, fecal coliforms, and total aerobic viable heterotrophic bacteria, but not with Kepone concentration, since Kepone-resistant bacteria were present in locations where Kepone could not be detected by the analytical methods used in this study. Only gram-negative bacteria, predominantly Pseudomonas, Vibrio, and Aeromonas spp., were found to be resistant to ≥10 μg of Kepone per ml. Gram-positive bacteria, i.e., Bacillus and Corynebacterium spp., were generally sensitive to ≥0.1 μg of Kepone per ml. From results of cluster analysis of taxonomic data, we determined that characteristics of Kepone-resistant bacteria included: resistance to pesticides and heavy metals; degradation of oil; positive oxidase and catalase reactions; and nitrate reduction. From results of the ecological and taxonomic analyses, we conclude that Kepone resistance in estuarine bacteria is due to the physicochemical composition of the gram-negative cell wall and not prior exposure to Kepone. Therefore, the presence of Kepone-resistant bacteria cannot serve as an indicator of Kepone contamination in the aquatic environment where gram-negative bacteria are predominant.